IMPACT OF WHEY BIOACTIVE HYDROLYSATES ON THE QUALITY OF FAT FILLINGS FOR CONFECTIONERY PRODUCTS - Stožinić, Milica; Zarić, Danica; Rakin, Marica; Lončarević, Ivana; Pajin, Biljana; Bulatović, Maja (Food and Feed Research, 2024)
Whey protein hydrolysates can be used in a wide range of applications because they offer numerous advantages compared to non-hydrolyzed whey proteins. They are more heat stable, with improved foaming and emulsifying properties due to the presence of bioactive peptides of lower viscosity. Whey hydrolysates have improved absorption, digestibility, excellent nutritional and functional properties, and the ability to extend the shelf life of food products. Due to the large differences in the technological and other physicochemical properties of hydrolysates, the addition of whey protein hydrolysates into confectionery products is much more complicated. This research aims to determine the possibilities of enriching filled confectionery products with whey peptides obtained in two ways:  through enzymatic hydrolysis of whey protein concentrate and fermentation (using microorganism Lb. rhamnosus ATCC 7469). Peptides were added to a fatty milk cream at a 5% concentration. The study was focused on assessing antioxidant activity, physical, rheological, textural, and sensory properties of three fat fillings: C (control without whey peptides), EWP (5% peptides from enzymatic hydrolysis), and MWP (5% peptides from whey fermentation).Enzymatic hydrolysates increased DPPH radical inhibition by 32%, and fermented hydrolysates by 19%. Enzymatic hydrolysates also demonstrated superior inhibition of lipid peroxidation (IC50 value of 811.54 mg mL-1) compared to fermented hydrolysates (IC50 value of 178.36 mg mL-1). EWP showed the highest antioxidant activity. Addition of enzymatic hydrolysates increased filling firmness by 2.5 times, while fermented hydrolysates had reduced firmness compared to the control. Both types of hydrolysates did not adversely affect the size or distribution of the particles in the fat cream. Thixotropic properties of the fat filling remained unchanged post-incorporation. MWP exhibited the most optimal rheological characteristics with the lowest yield stress. The best sensory characteristics (better than control sample) were found in the EWP.
Keywords: enzymatic hydrolysis; microbial hydrolysis; rheology; whey protein; antioxidant activity